Relationship between Specific Accruals and Disclosed Accounting results of companies in financial failure (Global Journal of Management and Business Research, 2018)
The display of net counter-performance (explained by the existence and persistence of negative accruals) can help leaders to convince partners of the need to renegotiate contracts. The importance of the measurement of the earnings management lies, for the most part, in the suspicion of undervaluation of debts and losses. This suspicion is so persistent that this risk of undervaluation must be taken into account in the valuation of any business. Nevertheless, we have tried through this article to test the approach of the models of specific accruals in order to identify them and to measure their impacts on the modification of the published result. Indeed, three models were tested, that is, that of receivables, inventories and amortization and provisions, which allowed us to validate the hypothesis according to which the managers of financially failing companies tend to exploit the Discretionary Accruals in an upward management goal to circumvent the costs of financial distress and change the perception of risk by its partners, especially donors. Based on this approach by the specific accruals, we have developed the model (4) which incorporates the specific discretionary accruals as explanatory variables of the formation of the published net result.
Keywords: earnings management; specific accruals; financial failure